Promoting educator wellbeing: the relationship between political skill, community empowerment, and collective leadership - Urick, Angela; Magnusen, Marshall; Eckert, Jonathan; Carpenter, Bradley (Frontiers in Education, 2025)
PurposeRecent demands placed on educators to navigate crises in schools have further solidified the urgency to promote wellbeing. The purpose of this study is to understand how to promote wellbeing for teachers and administrators with collective leadership through political skill and community empowerment.Research methodsWe surveyed N = 314 teachers and administrators in a central region of Texas during Fall 2021 to understand their influence and wellbeing during the COVID-19 pandemic. Educators were invited to participate in this survey, which included four instruments, and was collected using an email list through an educational service center when schools opened after quarantine. This survey data was applied to a multigroup structural equation model to demonstrate how factors lead to wellbeing. Teachers and administrators were compared to show varying relationships between responses about wellbeing, political skill, community empowerment, and collective leadership.FindingsThis study provides evidence to validate relationships between an interdisciplinary set of measures across these roles of educators. For teachers, as hypothesized, collective leadership and political skill influenced wellbeing. Community empowerment was a direct outcome for collective leadership but not wellbeing. For administrators, the hypothesized relationships had similar results. Collective leadership and political skill influenced wellbeing. Uniquely, in the structural phase of model testing, a path modification was added, which could be justified by theory, and specific to the role of administrators. Physical health was specified as a predictor of community empowerment. Overall, for both groups, collective leadership was situated as the main driver of this wellbeing model. Our findings reflect the importance of mixing positive psychology and leadership frameworks to understand how to support educators through a crisis.ImplicationsWe explain how collective leadership can provide educators with the agency necessary to promote their own wellbeing.